2021
DOI: 10.1111/mec.15860
|View full text |Cite
|
Sign up to set email alerts
|

Genomic signatures of clonality in the deep water kelp Laminaria rodriguezii

Abstract: Partial clonality, mode of reproduction, heterozygote excess, population genomics, kelp The development of population genomic approaches in non-model species allows for renewed studies of the impact of reproductive systems and genetic drift on population diversity. Here, we investigate the genomic signatures of partial clonality in the deep water kelp Laminaria rodriguezii, known to reproduce by both sexual and asexual means. We compared these results with the species Laminaria digitata, a closely related spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 90 publications
2
19
0
Order By: Relevance
“…This is well visible in strictly asexual organisms such as the Euglenozoa Trypanosoma brucei gambiense (Weir et al, 2016). Despite the difficulty to delineate clonal lineages, RAD-Seq offers new avenue in the study of the reproduction of partially clonal organisms, such as in the Kelp Laminaria rodriguezii (Reynes et al, 2021). Several points in our results show the effect of clonality in the studied populations.…”
Section: Signals Of Clonality With Rad-seq Datasupporting
confidence: 52%
“…This is well visible in strictly asexual organisms such as the Euglenozoa Trypanosoma brucei gambiense (Weir et al, 2016). Despite the difficulty to delineate clonal lineages, RAD-Seq offers new avenue in the study of the reproduction of partially clonal organisms, such as in the Kelp Laminaria rodriguezii (Reynes et al, 2021). Several points in our results show the effect of clonality in the studied populations.…”
Section: Signals Of Clonality With Rad-seq Datasupporting
confidence: 52%
“…All three populations exhibited strongly negative F IS values based on the SNP genotyping, but the most clonal population (Faro) exhibited the lowest F IS (-0.51). Negative F IS has been shown to be strongly linked to the degree of clonality in facultative sexually reproducing species driven by genetic drift, both in theoretical ( Prugnolle and De Meeûs, 2008 ) and population genetic assessments ( Arnaud-Haond et al, 2020 ; Reynes et al, 2021b ). Moreover, F IS has been shown to be not as sampling-sensitive as genotypic richness (R) and has been suggested as the measure of choice for assessing the importance of clonal reproduction in seagrasses ( Arnaud-Haond et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In L. rodriguezii, Reynes et al 2021 demonstrated that SNPs markers were indeed highly efficient to investigate partial clonality under a population genomic approach, and identified a particularly high level of genetic differentiation in comparison to other kelps. Nevertheless, the use of SNPs from RRS is far more expensive compared to microsatellite genotyping and their study was restricted to a rather small number of individuals (N = 43).…”
Section: Potential Uses Of the New Developed Microsatellites And Species Identification Markersmentioning
confidence: 99%
“…This could be particularly interesting for L. pallida, which has not been investigated so far despite its ecological importance and biogeographical significance. For L. rodriguezii, genetic diversity within populations was until now only investigated using more than 4000 SNPs (Reynes et al 2021).…”
Section: Potential Uses Of the New Developed Microsatellites And Species Identification Markersmentioning
confidence: 99%
See 1 more Smart Citation